Evaluation of the external and internal workload in female futsal players - Marco Beato; Giuseppe Coratella; Federico Schena; Andrew T. Hulton (Termedia Publishing House, 2017)
Match analysis technology has been extensively used in football, but there is limited literature on its use in futsal. Despite its increased popularity, the female futsal game model has never been quantified. The aim of this study was to quantify locomotor and mechanical activities performed during a non-competitive female futsal match, measuring the differences between the first and second half. Sixteen female futsal players of the Italian 2nd division were enrolled (age 27±5 years, height 1.65±0.09 m, body weight 56.9±7.7 kg, BMI 20.9±1.9, fat mass 21.5±2.9%). Locomotor and mechanical activities were recorded by means of the 10 Hz GPS StatSports system. Games were performed on a 38x18 m synthetic grass outdoor pitch. Significant differences were found between the first and second half in total distance (1424±114 and 1313±113 m, p<0.05), relative velocity (70±6 and 64±6 m min-1, p<0.05), high speed running (28±16 and 22±19 m, p<0.05) and high metabolic distance (80 ± 29 and 69 ± 28 m, p<0.05). The match analysis of female futsal matches provides useful information about its external load demands. Female futsal players decreased the workload in the second half compared to the first one during this non-competitive match. It was found that fatigue impairs the performance in the second part of the game. Coaches and physical trainers can obtain useful information to design training programmes taking into account the quantification of locomotor and mechanical activities performed in this study.